Usability Evaluation of Mobile Health Application from AI Perspective in Rural Areas of Pakistan - Samad Dahri, Abdul; Al-Athwari, Ahmad; Hussain, Azham (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Purpose: This study endorses AI enabled Mobile Health application and investigates usability evaluation of the Mobile Health application by patients’ task performance evaluation and satisfaction. Materials and Methods: International Organization for Standards (ISO) 9241-11 standard metrics were used and 15 patients performed tasks on task success rate, errors, efficiency (time spent), satisfaction (SUS scale). Results: Getting registered was a top easy task while finding a relevant doctor was the most difficult task for users. The satisfaction scores by SUS suggest good rather excellent application user experience. Male were successful task achievers, while educational level and mobile know-how influence the usability scores in terms of time consumed, task errors occurred, and task completed. Conclusion: Methods used in this study suggest future research from different contexts. Using ISO 9241-11 usability standards, the SUS instrument for satisfaction, and measuring user characteristics influence performance and can provide considerable Mobile Health design.